2020
DOI: 10.4209/aaqr.2020.06.0297
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in the Air Quality Index and the Impact of the COVID-19 Event on Air Quality in Western China

Abstract: This study investigated the AQI (air quality index) and atmospheric pollutants including PM 2.5 , PM 10 , CO, SO 2 , NO 2 and O 3 in Chongqing, Luzhou and Chengdu from 2017 to 2019. In addition, the impacts of the COVID-19 event on the air quality in the three cities in 2020 were compared and discussed. For the combined AQIs for the three cities, in spring, the daily AQIs ranged between 25 and 182 and averaged 72.1. In summer, the daily AQIs ranged between 24 and 206 and averaged 77.5. In autumn, the daily AQI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
(29 reference statements)
4
29
0
1
Order By: Relevance
“…The values of AQI, NO2, PM2.5, PM10, and CO from 1-19 January 2020 declined 19.4%, 17.0%, 27.5%, 15.8%, and 25.7%, respectively, compared with the same time periods in 2016-2019. The trends are consistent with the results in other regions in China(Chen et al, 2020;Xu et al, 2020;Filonchyk et al, 2020;Zhang et al, 2020a;Zhang et al, 2020b;Wan et al, 2020;Bao and Zhang, 2020). Different time periods of analysis contribute to the differences of our results from those of other studies.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 1 more Smart Citation
“…The values of AQI, NO2, PM2.5, PM10, and CO from 1-19 January 2020 declined 19.4%, 17.0%, 27.5%, 15.8%, and 25.7%, respectively, compared with the same time periods in 2016-2019. The trends are consistent with the results in other regions in China(Chen et al, 2020;Xu et al, 2020;Filonchyk et al, 2020;Zhang et al, 2020a;Zhang et al, 2020b;Wan et al, 2020;Bao and Zhang, 2020). Different time periods of analysis contribute to the differences of our results from those of other studies.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…the COVID-19 pandemic (Chen et al, 2020;Xu et al, 2020;Filonchyk et al, 2020;Zhang et al, 2020a;Zhang et al, 2020b;Wan et al, 2020;Bao and Zhang, 2020). Similar reductions have been observed in other regions of the world.…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…S4, the time lag between the O 3 and PM 2.5 trendlines and the presence of isolated peaks in O 3 , suggest there were significant contributions to local O 3 concentrations derived from changes in UK emissions. Importantly, these findings are not limited to the UK, with other studies from a range of countries also showing that tropospheric O 3 concentrations increased owing to changes in emissions profiles during lockdown, including in Spain ( Tobías et al, 2020 ), Brazil ( Siciliano et al, 2020 ), Italy, ( Sicard et al, 2020 ), China ( Chen et al, 2020 ; Le et al, 2020 ; Zhang et al, 2020 ), Korea ( Ju et al, 2020 ) and India ( Sharma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 58%
“…The O 3 concentration decreased by 16.4% and 33.9% in Beijing and Tianjin, respectively, but increased by 16.6% in Shijiazhuang. Related studies also found that the average O 3 concentration increased during the COVID-19 outbreak compared to 2017–2019 in Hubei Province ( Xu et al., 2020 ), western China ( Zhang et al., 2020a ), and 366 urban areas across mainland China ( Chen et al., 2020b ). An increased O 3 concentration is believed to be mainly due to the reduced NO 2 that hinders the reaction between NO and O 3 , thus increasing the atmospheric oxidizing capacity ( Le et al., 2020 ; Nichol et al., 2020 ; Xu et al., 2020 ).…”
Section: Resultsmentioning
confidence: 89%